Finding ways (and words) to move: Mad student politics and practices of loneliness. Issue 7 (14th September 2019) - de Bie, Alise
Abstract: By blending the conceptual frameworks of epistemic injustice and ethical loneliness and applying them to campus-based practices of 'risk' identification and 'referral', this article describes how Mad students come to be abandoned as knowers and learners. I then dwell in and politicize the condition of (ethical) loneliness these harms produce by seeking to 'practise' it as a form of Mad knowing, and as a framework for visioning justice. Framing Mad student experiences in this way opens up several possibilities for epistemic justice. First, it offers additional language and interpretive resources for naming and protesting our experiences of violence. Second, it compels us to understand and attend to Mad student experiences of epistemic harm and to recognize how Mad knowledges are routinely generated in their wake. Third, it invites new ways of understanding and responding to these harms, and imagining redress.